Estimate Sediment Thickness in Air Sempiang Village, Kepahiang Using the HVSR Method and the f0 and A0 Values - Hafiza, Belliya; S, Vionita; Rabbani, Muhammad Rifqi; Suhendra, Suhendra; Sihombing, Yezra Tariza; Valennita, Valennita; Febriansyah, Gian Ori (Universitas Negeri Gorontalo, 2026)
Microtremor-based site characterization provides rapid constraints on near-surface stratigraphy where borehole or geotechnical data are limited. This study estimates relative sediment-thickness variation and site response in Air Sempiang Village (Kabawetan District, Kepahiang Regency, Bengkulu Province, Indonesia) using the horizontal-to-vertical spectral ratio (HVSR) method and the derived dominant frequency (f₀) and amplification factor (A₀). Ambient-vibration data were acquired at 13 measurement points (30 min per site) using a PASIGemini-2 three-component geophone. HVSR processing was performed in Geopsy 3.2.2, including time-window selection, spectral smoothing, and peak identification to obtain f₀ and A₀. The resulting parameters were interpolated using inverse distance weighting in ArcGIS to generate spatial distribution maps. The estimated dominant frequencies are predominantly high (approximately 7–20 Hz), indicating generally shallow sediment cover and relatively stiff near-surface conditions, with localized lower-f₀ zones interpreted as thicker sediment accumulations. Amplification factors vary from 2 to 8, with moderate-to-high amplification concentrated in areas inferred to contain softer or thicker sediments, whereas lower A₀ values coincide with zones interpreted as being closer to competent bedrock. The combined f₀–A₀ patterns delineate subareas that are more susceptible to medium- to high-frequency ground-motion amplification and provide a first-order basis for local-scale seismic microzonation and earthquake risk mitigation planning in the study area.